2003
DOI: 10.2105/ajph.93.10.1694
|View full text |Cite
|
Sign up to set email alerts
|

Health Behaviors and Quality of Care Among Latinos With Diabetes in Managed Care

Abstract: Objectives. We evaluated whether ethnicity and language are associated with diabetes care for Latinos in managed care.Methods. Using data from 4685 individuals in the Translating Research Into Action for Diabetes (TRIAD) Study, a multicenter study of diabetes care in managed care, we constructed multivariate regression models to compare health behaviors, processes of care, and intermediate outcomes for Whites and English-and Spanish-speaking Latinos.Results. Latinos had lower rates of self-monitoring of blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 20 publications
(13 reference statements)
3
56
1
Order By: Relevance
“…Two other studies, after adjusting extensively, reported different outcomes in glycemic control. One study (60) demonstrated no ethnic differences in glycemic control, while another study (50) showed worse control among Hispanics. Overall, intermediate outcomes of care were worse in blacks, and outcomes among Hispanics were inclined to be worse.…”
Section: Ethnic Differences In Intermediate Outcomes Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…Two other studies, after adjusting extensively, reported different outcomes in glycemic control. One study (60) demonstrated no ethnic differences in glycemic control, while another study (50) showed worse control among Hispanics. Overall, intermediate outcomes of care were worse in blacks, and outcomes among Hispanics were inclined to be worse.…”
Section: Ethnic Differences In Intermediate Outcomes Of Carementioning
confidence: 99%
“…One study (54) reported equal quality of care (process of care) for blacks, and three studies (15, 32,55) noted predominantly a higher quality of care for blacks. For Hispanics, two studies (32,54) reported equal quality of process of care, two studies (14,64) reported lower quality, and one study (50) higher quality. One study (61) involved non-English-speaking Asians (56% of the Asians compared with 7% of whites were non-English speaking).…”
Section: Ethnic Differences In Quality Of Carementioning
confidence: 99%
“…Adherence may be improved by using a once-daily versus twice-daily basal insulin; however, as the insulin regimen continues to be adjusted, the total number of injections per day may counter this benefit, as The significant difference in HbA 1c values between Hispanics and whites observed in our study has been reported elsewhere. [30][31][32][33] The results of the regression model exploring patients' characteristics on refill frequency are revealing. Patients who are female, black, Hispanic, or of Native American heritage obtain fewer refills than do those who are white or Asian.…”
Section: Discussionmentioning
confidence: 99%
“…There also is a relationship between Hispanic adults with type 2 Diabetes and poorer glycemic control [5]. Hispanic individuals experience more complications related to their diabetes and difficulty with self-management compared to their Caucasian adult counterparts [5][6].…”
mentioning
confidence: 99%
“…Hispanic individuals experience more complications related to their diabetes and difficulty with self-management compared to their Caucasian adult counterparts [5][6]. Disparities in the experiences of Hispanics and Caucasians result in variances in the respective groups' access to health-care services, as well as their utilization of these services.…”
mentioning
confidence: 99%